Technical Writing and Simple Statistics for laboratory classes - Wettstein, Stephanie G. (Open textbook library., 2022)
This upper division resource focuses on how to communicate results through technical writing, use Excel to perform simple statistics, and create professional charts/documents. Excel tutorials are provided for performing descriptive statistics, t-tests, and linear regression as well as using text boxes, formatting figures and captions, and using Equation Editor to insert equations. Additionally, guidance and examples of different communication components are provided along with team writing strategies and guidelines on how to hold efficient meetings. This textbook was designed for Biology and Chemistry majors for a 400 level course.